2011
DOI: 10.1007/s11670-011-0306-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of promoter hypermethylation of Retinoic Acid Receptor Beta (RARB) and CDKN2 (p16/MTS1) in prostate cancer

Abstract: Objective: The molecular mechanism of prostate cancer is poorly understood. The aim of the study was to investigate the prevalence and prognostic value of promoter hypermethylation of retinoic acid receptor beta (RARB) and p16 among benign prostatic hyperplasia (BPH) and prostate cancer patients.Methods: In this case-control study, 63 patients were included in three groups; 21 with BPH as the control group, 21 with prostate cancer and good prognostic factors (based on prostate-specific antigen, Gleason score a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 32 publications
2
25
0
1
Order By: Relevance
“…In our study, AA can also down-regulate AR through supressing p300. Androgen is involved in cell cycle progression at G1/S transition and androgen depletion of LNCaP cells resulted in G1 arrest of the cell cycle with suppression of cyclin D1 expression and CDK4 activity (17). Androgen plays a key role in the development of prostate cancer through AR signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, AA can also down-regulate AR through supressing p300. Androgen is involved in cell cycle progression at G1/S transition and androgen depletion of LNCaP cells resulted in G1 arrest of the cell cycle with suppression of cyclin D1 expression and CDK4 activity (17). Androgen plays a key role in the development of prostate cancer through AR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Androgen is an important biological effector of prostate cancer progression (17). Many studies have demonstrated that phytochemicals can effectively inhibit the apoptosis and proliferation of prostate cancer cells (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…This alteration has been detected in many studies [25, 28, 34, 38], although some have reported controversial results [27, 29, 36]. Cho, NY et al [26].…”
Section: Discussionmentioning
confidence: 99%
“…Reactivation of p16 INK4a will likely be of clinical benefit to cancer patients as its expression has been associated with longer disease-free survival and better prognosis in human breast cancer (35). In addition, the prognostic value of determining p16 INK4a promoter methylation has been reported for breast (7) and prostate cancers (8). Further in vivo studies are needed to evaluate the possible benefits of combining EGCG with a clinically useful HDAC inhibitor, such as suberoylanilide hydroxamic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation of p16 INK4a may be an early event in carcinogenesis (7). Further more, the detection of p16 INK4a hypermethylation at higher concentrations in the plasma of breast cancer patients than in healthy control patients suggests that it may be a suitable tool for cancer screening, and its prognostic value has been suggested for breast and prostate cancer patients (7,8).…”
Section: Introductionmentioning
confidence: 99%